2022
DOI: 10.3389/fcvm.2022.979431
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment strategies for patients with type A aortic dissection involving arch anomalies

Abstract: ObjectiveThe aim of the study was to investigate surgical modalities and outcomes in patients with type A aortic dissection involving arch anomalies.MethodPatients with type A aortic dissection who underwent surgical treatment at our center between January 2017 and 31 December 2020 were selected for this retrospective analysis. Data including computed tomography (CT), surgical records, and cardiopulmonary bypass records were analyzed. Perioperatively survived patients were followed up, and long-term mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…Regarding the implications of surgical treatment of AADA in patients with BAAs, the perioperative mortality rate recorded in the cohort studied by Zhu et al [36] is somewhat consistent with previous studies conducted by Ma et al [53] and Waterford et al [54] who concluded that the documented perioperative mortality rate in patients with AADA was between 5 and 15%. There is research reporting a higher frequency of neurological problems in patients with AADA [41], which is consistent with the findings of the studies included in our review that patients with AADA experienced more neurological complications and perioperative deaths compared to those with various AA abnormalities.…”
Section: Potential Risks Associated With Endovascular Interventional ...supporting
confidence: 85%
See 2 more Smart Citations
“…Regarding the implications of surgical treatment of AADA in patients with BAAs, the perioperative mortality rate recorded in the cohort studied by Zhu et al [36] is somewhat consistent with previous studies conducted by Ma et al [53] and Waterford et al [54] who concluded that the documented perioperative mortality rate in patients with AADA was between 5 and 15%. There is research reporting a higher frequency of neurological problems in patients with AADA [41], which is consistent with the findings of the studies included in our review that patients with AADA experienced more neurological complications and perioperative deaths compared to those with various AA abnormalities.…”
Section: Potential Risks Associated With Endovascular Interventional ...supporting
confidence: 85%
“…Zhu et al [36] found that in patients with BAAs undergoing surgical treatment for AADA, the perioperative mortality rate aligns with rates reported in previous studies by Ma et al [53] and Waterford et al [54], which indicated a mortality rate of 5-15%. One study [23] showed a higher likelihood of neurological adverse events in patients with BAAs, which was supported by the findings of Zhu et al [36], who reported higher rates of neuro-related complications and perioperative fatality rate in patients with BAAs compared to those with different other anomalies.…”
Section: Potential Risks Associated With Endovascular Interventional ...supporting
confidence: 77%
See 1 more Smart Citation